Research Themes for Islamic Tourism - Md Sawari, Siti Salwa (Kulliyyah of Languages Management, 2022)
The intent of this book is to give you some insights on current research on Islamic Tourism in Malaysia. Its demonstration an empirical research trend in Islamic Tourism among the tourist in Malaysia. The research topic cover on DIY Umrah, Religious Tourism, Muslim Friendly Tourism, Spiritual Tourism and Hospitality.